The Communicative Approach to Language Teaching: Implications for the Teaching of Tami - Rajagopal, Subramaniam (Journal of Modern Languages, 2017)
This study considers the relevance of the communicative approach to the teaching of Tamil as a native or first language, as a second, third or foreign language. The paper also considers the different methods of teaching Tamil language in schools, especially in primary schools.